Trends Of Facebook Use Among University Students In Pakistan - Mahmood, Zubair; Ahmad, Jamilah (2015)
Facebook has been adapted as a platform for connecting with friends, sharing information, a favorite past time, and a way of new entertainment by much of the youth in Pakistan. Over 12 million people in Pakistan, half of whom fall between the ages of 18 to 30, use Facebook. This study aims to investigate the Trends of Facebook uses among students in universities of Pakistan. A qualitative study conducted for this purpose and three focus group discussions have been conducted involving postgraduate students from three different universities in Pakistan, who are using Facebook more than 2 hours daily. Findings from thematic analysis shows that most of the students are of the view that they are using Facebook for social interactions, information sharing/seeking, entertainment, pass time and to stay in touch with old friends and searching for new friends. Moreover result shows that students are using Facebook for relaxation after their hectic life routine and in boring classes.